Hydrocephalus, Situs Inversus, Chronic Sinusitis, and Male Infertility in DNA Polymerase λ-Deficient Mice: Possible Implication for the Pathogenesis of Immotile Cilia Syndrome - Kobayashi, Yosuke (American Society for Microbiology, 2002)
A growing number of DNA polymerases have been identified, although their physiological function and relation to human disease remain mostly unknown. DNA polymerase λ (Pol λ; also known as Pol β2) has recently been identified as a member of the X family of DNA polymerases and shares 32% amino acid sequence identity with DNA Pol β within the polymerase domain. With the use of homologous recombination, we generated Pol λ(−/−) mice. Pol λ(−/−) mice develop hydrocephalus with marked dilation of the lateral ventricles and exhibit a high rate of mortality after birth, although embryonic development appears normal. Pol λ(−/−) mice also show situs inversus totalis and chronic suppurative sinusitis. The surviving male, but not female, Pol λ(−/−) mice are sterile as a result of spermatozoal immobility. Microinjection of sperm from male Pol λ(−/−) mice into oocytes gives rise to normal offspring, suggesting that the meiotic process is not impaired. Ultrastructural analysis reveals that inner dynein arms of cilia from both the ependymal cell layer and respiratory epithelium are defective, which may underlie the pathogenesis of hydrocephalus, situs inversus totalis, chronic sinusitis, and male infertility. Sensitivity of Pol λ(−/−) cells to various kinds of DNA damage is indistinguishable from that of Pol λ(+/+) cells. Collectively, Pol λ(−/−) mice may provide a useful model for clarifying the pathogenesis of immotile cilia syndrome.